PELATIHAN PENINGKATAN VALUE PRODUK DAN MANAJEMEN KEUANGAN PADA UNIT USAHA PERIKANAN PESANTREN BISNIS ORENZ - Aditya Prima Yudha; Arie Wibowo Irawan; Dwi Meyliani Riswanti (Rural Development For Economic Resilience (RUDENCE), 2022)
The most varied Islamic educational institutions are pesantren, given the freedom of the founding kyai to express pesantren with an emphasis on certain fields. Pesantren which is the hope of the community as a place to study in the hope that it can be a provision in the face of the times. However, the pesantren itself also faces many problems. Among the input problems contained in Islamic boarding schools are the weaknesses of the vision and goals brought by pesantren education. The Orenz business boarding school is a modern Islamic boarding school in Leuwiliang sub-district, Bogor Regency. This Islamic boarding school has a vision to produce students who master religious knowledge well and are independent by entrepreneurship. The operational needs of the pesantren are met from the business units that are built. The concept of a modern business boarding school must be supported by good governance and management. The problem that occurs is that the income obtained from the business unit is not maximized, especially from the aquaculture business unit. The business management carried out is also not supported by good financial management skills, especially in making financial reports. In order to increase the ability and business capacity of the Orenz Islamic Boarding School, it is necessary to conduct training in increasing the value of the products produced and financial management training.